A systematic review of selected caries prevention and management methods - Bader JD, Shugars DA, Bonito AJ (Blackwell Synergy, 2001)
A systematic review of the periodic scientific literature was undertaken to determine the strength of the evidence for the efficacy of professional caries preventive methods applied to high risk individuals, and the efficacy of professionally applied methods to arrest or reverse non-cavitated carious lesions.